Chorioamnionitis and Chronic Lung Disease of Prematurity: A Path Analysis of Causality - Dessardo, Nada Sindičić; Mustać, Elvira; Dessardo, Sandro; Banac, Srđan; Peter, Branimir; Finderle, Aleksandar; Marić, Marinko; Haller, Herman (American Journal of Perinatology, 2012)
Current evidence suggests that additional pathogenetic factors could play a role in the development of chronic lung disease of prematurity, other than mechanical ventilation and free radical injury. The introduction of the concept of “fetal inflammatory response syndrome” offers a new perspective on the pathogenesis of chronic lung disease of prematurity. New statistical approaches could be useful tools in evaluating causal relationships in the development of chronic morbidity in preterm infants. The aim of this study was to test a new statistical framework incorporating path analysis to evaluate causality between exposure to chorioamnionitis and fetal inflammatory response syndrome and the development of chronic lung disease of prematurity. We designed a prospective cohort study that included consecutively born premature infants less than 32 weeks of gestation whose placentas were collected for histological analysis. Histological chorioamnionitis, clinical data, and neonatal outcomes were related to chronic lung disease. Along with standard statistical methods, a path analysis was performed to test the relationship between histological chorioamnionitis, gestational age, mechanical ventilation, and development of chronic lung disease of prematurity. Among the newborns enrolled in the study, 69/189 (36%) had histological chorioamnionitis. Of those with histological chorioamnionitis, 28/69 (37%) were classified as having fetal inflammatory response syndrome, according to the presence of severe chorioamnionitis and funisitis. Histological chorioamnionitis was associated with a lower birth weight, shorter gestation, higher frequency of patent ductus arteriosus, greater use of surfactant, and higher frequency of chronic lung disease of prematurity. Severe chorioamnionitis and funisitis were significantly associated with lower birth weight, lower gestational age, lower Apgar score at 5 minutes, more frequent use of mechanical ventilatory support and surfactant, as well as higher frequency of patent ductus arteriosus and chronic lung disease. The results of the path analysis showed that fetal inflammatory response syndrome has a significant direct (0.66), indirect (0.11), and overall (0.77) effect on chronic lung disease. This study demonstrated a strong positive correlation between exposure of the fetus to a severe inflammatory response and the development of chronic lung disease of prematurity.
Keywords: chorioamnionitis; FIRS; chronic lung disease; prematurity